A water-soluble lutein composite nanoparticle and preparation method thereof
The synthesis of lutein graft copolymers by Steglich esterification method solved the problems of lutein water solubility and bioavailability, achieved efficient water solubility improvement and structural retention, and was suitable for industrial production.
Patent Information
- Application Number
- CN202310302133.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-03-27
AI Technical Summary
In the prior art, lutein has insufficient water solubility and bioavailability, and physical encapsulation and chemical modification modification methods have the problem of using a large number of emulsifiers and surfactants, resulting in limited potential risks and water solubility improvements in the product.
The grafted copolymer of lutein was synthesized under mild conditions by Steglich esterification. The solvent was removed by distillation under reduced pressure and the addition of deionized water was completed to complete self-assembly to prepare water-soluble lutein composite nanoparticles to improve their water solubility and biologicity. Utilization.
It has achieved high efficiency and water solubility of lutein, retained structure, increased drug loading, and improved biological accessibility, avoiding the damage to the structure by free radical polymerization. The process is simple and efficient, and is suitable for industrial production.
Smart Images

Figure CN116059386B_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a water-soluble lutein composite nanoparticle and a preparation method thereof, belonging to the technical field of pharmaceutical intermediates and preparation thereof. Background Art
[0002] The molecular formula of lutein is C 40 H 56 O2, molecular weight of 568.85, has 8 stereoisomers, 3 asymmetric chiral centers, soluble in acetone, dichloromethane, tetrahydrofuran, chloroform, insoluble in water. Lutein, as a natural carotenoid, is mainly found in marigold flowers, egg yolks, corn, broccoli and other vegetables. Studies have found that lutein is abundant in the human retina. Due to its ability to absorb harmful blue light, it plays a decisive role in preventing eye diseases such as cataracts and age-related macular degeneration. In addition to the eyes, lutein is also found in other tissues. Its inherent antioxidant properties also mean that it can protect cells in the human body from damage by free radicals, and plays an important role in combating tissue inflammation and preventing skin damage caused by ultraviolet rays. In industry, lutein is also used as a natural pigment and food additive. These unique physiological properties of lutein make it increasingly valued in the research and development of medical health care and functional foods, and its application prospects are broad.
[0003] However, lutein cannot be synthesized in the human body, and dietary intake is the only source. In addition, the hydroxyl groups at both ends of lutein are easily oxidized and photolyzed, and are unstable in nature and easily affected by some physical and chemical factors such as acid, high temperature, high humidity, air, and light. This makes it easy to degrade when exposed to light, oxygen, and heat, and it has poor water solubility and is easily oxidized and ineffective. Studies have shown that although many foods contain high levels of lutein, most of the lutein is difficult to be incorporated into the micelle phase and absorbed and utilized during the digestion process due to the above shortcomings. Therefore, in order to expand the application of lutein in the food and medical fields, one of the main problems that need to be solved is to improve the water solubility and bioavailability of lutein.
[0004] To this end, the prior art has developed a technical solution to improve the water solubility of lutein. In terms of improving the water solubility, chemical stability and bioavailability of lutein, domestic and foreign researchers mainly adopt two methods: physical encapsulation and chemical modification. Physical encapsulation modification usually refers to the process of embedding or coating the active material in the wall material. This method improves the stability of lutein by establishing a barrier between lutein and the external environment. If physical encapsulation is distinguished by the type of encapsulation, it mainly includes: liposome system, emulsion system and block copolymer micelle system. The problem with this method is that a large amount of emulsifier is required, or the preparation of block copolymer micelles is complicated and the drug loading is low. Chinese patent CN102475696 A discloses a water-soluble lutein and its preparation process, and its prescription composition and weight ratio are lutein powder: emulsifier: additive = 1:2~20:0~5. The dissolution rate of lutein in the water-soluble lutein powder prepared by the solvent-free reduced pressure melting method can reach 98%, and it has good water solubility, high stability and good dispersibility. Chinese patent CN 103860476 B discloses a water-soluble powder and a preparation method thereof, wherein lutein, a water-soluble carrier, a surfactant and an additive are dissolved in an organic solvent at a weight ratio of 1:5-20:1-5:0-3 at 20-60°C, and spray-dried after being completely dissolved. The obtained lutein water-soluble powder has high water solubility, strong stability, uniform and lasting color, good fluidity, and a solubility in water of more than 95%. Chinese patent CN 104434814 A discloses a water-soluble lutein granule and a preparation process and application thereof, wherein a mixed powder of lutein and a water-soluble polymer auxiliary material is recrystallized using a CO2 supercritical fluid to obtain a water-soluble lutein granule. Chinese patent CN 107137383 A discloses a method and product for preparing water-soluble lutein by low-temperature melt extrusion, wherein lutein is mixed with a non-ionic polymer surfactant and then extruded under certain conditions by a hot melt extruder.
[0005] The chemical modification of lutein mainly utilizes the hydroxyl groups at both ends for chemical reaction modification, which has limited effect on improving water solubility. For example, Chinese patent CN 106543323 B discloses a polycarotenoid acrylate blue light absorber and its preparation method, wherein the polycarotenoid acrylate is prepared from carotenoid to obtain carotenoid acrylate, and then the carotenoid acrylate is polymerized to obtain a polyacrylic acid carotenoid ester solid. It is proposed to first synthesize an acrylate monomer containing lutein, and then perform free radical polymerization to obtain a graft copolymer. The defect of this method is that in the free radical polymerization process, lutein acts as a free radical scavenger, and the carbon-carbon double bond in its structure reacts rapidly with the free radical, and the structure is completely destroyed. In addition, the obtained graft copolymer does not contain a hydrophilic group and is completely insoluble in water.
[0006] Although the above scheme improves the water solubility of lutein, it also has certain technical problems: a large amount of emulsifiers, surfactants, and stabilizers are used, and some of them have harmful solvent residues, which brings potential risks to the final product; and the prepared water-soluble lutein is actually physically dispersed to form nanoparticles; the water solubility of the obtained lutein is limited.
[0007] Therefore, a method for preparing new water-soluble lutein composite nanoparticles from natural lutein with good water solubility, stable properties, mild reaction conditions, and suitability for industrialization is urgently needed to be studied and developed. Summary of the invention
[0008] The purpose of the present invention is to provide a method for preparing new water-soluble lutein composite nanoparticles from natural lutein with mild reaction conditions and suitable for industrialization, so that it can be widely used in the fields of food and medicine.
[0009] In order to achieve the purpose of the invention, the technical solution adopted by the present invention is: the polyacrylic acid is refluxed in advance to remove the possible residual oxidative initiator, and after freeze drying, the polyacrylic acid is dissolved in anhydrous tetrahydrofuran. Then, the lutein graft copolymer is synthesized under mild conditions by the Steglich esterification method. Finally, the solvent is removed by vacuum distillation, and deionized water is added thereto to complete the self-assembly of the amphiphilic lutein graft copolymer and the physical loading of the unreacted lutein, so as to prepare water-soluble lutein composite nanoparticles.
[0010] The specific steps of the present invention are:
[0011] S1: Dissolve polyacrylic acid in water to prepare an aqueous solution with a mass concentration of 30%, and reflux for a period of time to remove the existing oxidizing initiator.
[0012] S2: freeze-dry the polyacrylic acid solution obtained by reflux in step S1 for 24 hours, and then dissolve it in a certain amount of anhydrous tetrahydrofuran solution for later use.
[0013] S3: adding a certain amount of lutein, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to the solution prepared in step S2, stirring and reacting for a certain time at a certain temperature in the dark, and setting aside.
[0014] S4: The solvent after the reaction in step S3 was evaporated by reduced pressure distillation at 45°C for 1 hour, and deionized water of the same volume as the solution prepared in step S2 was added thereto to complete the self-assembly of the amphiphilic copolymer, and water-soluble lutein composite nanoparticles were prepared by freeze drying for 24 hours.
[0015] Preferably, the reflux time in step S1 is 6 to 24 hours.
[0016] Preferably, the mass ratio of anhydrous tetrahydrofuran to polyacrylic acid in step S2 is 10: 1 to 100: 1.
[0017] Preferably, in the mixed solution in step S3, the mass ratio of lutein to polyacrylic acid is 1:4 to 1:1, and the lutein is calculated as pure product.
[0018] Preferably, the mass ratio of lutein to dicyclohexylcarbodiimide and 4-dimethylaminopyridine in step S3 is 284:103-412:6.1, and the lutein is calculated as pure product.
[0019] Preferably, the stirring reaction temperature in step S3 is 25-45°C.
[0020] Preferably, the stirring reaction time in step S3 is 4 to 12 hours.
[0021] Another object of the present invention is to prepare a water-soluble lutein powder with good water solubility and stable properties by the above method; the powder can be made into tablets, capsules, powders, ointments or solutions, etc. by adding pharmaceutically or functional food acceptable excipients.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The method for preparing water-soluble lutein composite nanoparticles of the present invention adopts the Steglich esterification reaction of lutein and water-soluble high molecular weight polyacrylic acid to synthesize a graft copolymer with polyacrylic acid as the main chain and lutein as the side chain. The two are covalently bonded to improve the water solubility of lutein, so that it can be directly dissolved in water.
[0024] 2. In the method for preparing water-soluble lutein composite nanoparticles of the present invention, the lutein that has not been esterified during the reaction is encapsulated in situ in the micelles formed by the graft copolymer. Since the side chain of the graft copolymer is lutein, it has the greatest compatibility with the unreacted lutein, thereby increasing the drug loading. Moreover, since the obtained graft copolymer is partially esterified and contains many hydrophilic groups, it can be completely micellized and dissolved in water, greatly increasing the bioaccessibility and in vivo utilization rate.
[0025] 3. The method for preparing water-soluble lutein composite nanoparticles of the present invention does not go through a free radical polymerization process, thus avoiding the destruction of the lutein structure by the free radical polymerization reaction, and retaining the lutein structure to the greatest extent. The whole process is simple and efficient, the conditions are mild, and the system is simple and pure. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Other features and advantages of the present invention will become apparent from the following description made with reference to the accompanying drawings, in which:
[0027] Figure 1 It is the ultraviolet spectrum of the sample of Example 2;
[0028] Figure 2 The transmission electron microscope and particle size distribution diagram of the sample in Example 2;
[0029] Figure 3 This is a comparison chart of the saturated solubility and bioaccessibility of the samples in Example 2;
[0030] Figure 4 The pharmacokinetic experimental results of the sample in Example 2 in a mouse model.
[0031] in, Figure 1 a is lutein, b is lutein composite nanoparticles; Figure 2 a and b are lutein composite nanoparticles, d and e are pure lutein graft copolymers, c is lutein composite nanoparticles, and f is pure lutein graft copolymer; Figure 3 a is lutein, b is lutein composite nanoparticles, and c is commercially available water-soluble lutein micropowder; Figure 4 a is in mouse plasma, b is in liver, c is in mesenteric tissue, and d is in eyeball. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the examples, which are used to illustrate the present invention but are not intended to limit the scope of protection of the present invention. The conditions in the examples can be further adjusted according to specific conditions, and simple improvements to the method of the present invention under the premise of the concept of the present invention all belong to the scope of protection claimed in the present invention.
[0033] In the embodiment of the present invention, lutein (85%) and water-soluble lutein powder (5%) are from Shandong Tianyin Biotechnology Co., Ltd. Example 1
[0034] 50 parts of polyacrylic acid (Mw5000) were dissolved in water to prepare an aqueous solution with a mass concentration of 30%, and refluxed for 6 hours; after the reflux was completed, the polyacrylic acid solution was freeze-dried for 24 hours, and then dissolved in 500 parts of anhydrous tetrahydrofuran; 14.71 parts of lutein, 4.5 parts of dicyclohexylcarbodiimide and 0.268 parts of 4-dimethylaminopyridine were added thereto in sequence, and then stirred at 25°C in the dark for 4 hours; after the reaction was completed, the solvent was removed by reduced pressure distillation at 45°C for 1 hour, deionized water was added thereto for self-assembly of the amphiphilic copolymer, and water-soluble lutein composite nanoparticles were prepared after 24 hours of freeze drying, and the parts are all parts by mass. Example 2
[0035] 100 parts of polyacrylic acid (Mw5000) were dissolved in water to prepare an aqueous solution with a mass concentration of 30%, and refluxed for 12 hours; after the reflux was completed, the polyacrylic acid solution was freeze-dried for 24 hours, and then dissolved in 5000 parts of anhydrous tetrahydrofuran; 58.82 parts of lutein, 36.3 parts of dicyclohexylcarbodiimide and 1.074 parts of 4-dimethylaminopyridine were added thereto in sequence, and then stirred at 35°C in the dark for 8 hours; after the reaction was completed, the solvent was removed by reduced pressure distillation at 45°C for 1 hour, deionized water was added thereto for self-assembly of the amphiphilic copolymer, and water-soluble lutein composite nanoparticles were prepared after 24 hours of freeze drying, and the parts are all parts by mass. Example 3
[0036] 250 parts of polyacrylic acid (Mw5000) were dissolved in water to prepare an aqueous solution with a mass concentration of 30%, and refluxed for 24 hours; after the reflux was completed, the polyacrylic acid solution was freeze-dried for 24 hours, and then dissolved in 25000 parts of anhydrous tetrahydrofuran; 294.12 parts of lutein, 363.1 parts of dicyclohexylcarbodiimide and 5.372 parts of 4-dimethylaminopyridine were added thereto in sequence, and then stirred at 45°C in the dark for 12 hours; after the reaction was completed, the solvent was removed by reduced pressure distillation at 45°C for 1 hour, deionized water was added thereto for self-assembly of the amphiphilic copolymer, and water-soluble lutein composite nanoparticles were prepared after 24 hours of freeze drying, and the parts are all parts by mass.
[0037] The water-soluble lutein composite nanoparticles prepared in Example 2 were subjected to characterization tests:
[0038] 1. The absorption spectra of lutein and lutein composite nanoparticles were recorded using UV-visible spectrometer with ethanol as reference.
[0039] 2. The self-assembly morphology of lutein composite nanoparticles and pure lutein graft copolymers was observed by transmission electron microscopy at an accelerating voltage of 200 KV. The sample preparation method is: drop the self-assembly aqueous solution of the sample on a copper mesh covered with a carbon film, air dry it for 3 hours, and then vacuum dry it for 10 hours.
[0040] 3. Determine the saturated solubility of lutein monomer, lutein composite nanoparticles and commercially available water-soluble lutein micropowder with equal lutein content. Add deionized water at room temperature to 30 mg of sample, and the final volume is fixed to 5 mL. Stir in a sealed container in the dark for 24 h. Then centrifuge at 10,000 rpm for 5 min, filter the suspension through a filter membrane with a pore size of 0.45 μm, and collect the filtrate for freeze-drying. Determine the lutein content in the filtrate by measuring the absorbance.
[0041] 4. The bioaccessibility was calculated by constructing an in vitro simulated stomach and small intestine digestion process of lutein (lutein monomers with equal lutein content, lutein composite nanoparticles, and commercially available water-soluble lutein micropowders). The lutein extracted from the mixed solution at the end of the simulated digestion was then determined. Artificial gastric juice stock solution (2 g NaCl, 7 mL concentrated HCl (37% w / w) in 1 L distilled water) was prepared in advance. Before the digestion experiment, pepsin with a mass fraction of 0.32% was added to the artificial gastric juice stock solution and stirred in a 37°C water bath to prepare a pepsin working solution. The pepsin working solution was mixed with the lutein product, and the pH value was adjusted to 2.5 with NaOH solution. The mixture was placed in a 37°C constant temperature water bath and stirred in the dark under argon protection for digestion.
[0042] The pH of the digestive fluid after the gastric digestion stage was titrated to 7.0 using NaOH solution, and small intestinal salt solution (0.25 MCaCl2 and 3.0 M NaCl, dissolved in 50 mM KH2PO4 buffer) and bile salt solution (54 mg / mL porcine bile salt, dissolved in 50 mM KH2PO4 buffer) were added. After the digestive fluid was fully mixed, pancreatic enzyme working solution (24 mg / mL pancreatic enzyme, dissolved in 50 mM KH2PO4 buffer) was added to simulate digestion in the small intestine stage. During digestion, the pH was kept constant at 7.0, and the digestion was placed in a 37°C constant temperature water bath, and stirred and digested in the dark under argon protection.
[0043] The digested solution was centrifuged at 4°C, and the supernatant was transferred to a separatory funnel and extracted with n-hexane. After multiple extractions, the organic phases were combined and distilled under reduced pressure. The distillation substrate was dissolved in ethanol and transferred to a volumetric flask to a fixed volume. The amount of lutein digested in vitro was determined by measuring the absorbance.
[0044] 5. Male Kunming mice (8 weeks old, weighing 20-22 g) were purchased from Shandong Experimental Animal Center (Jinan, China) with license number SCXK 2020-0005. All animal procedures were performed in accordance with the Guide for the Care and Use of Laboratory Animals of Shandong University of Technology and approved by the Animal Ethics Committee of Shandong University of Technology. Mice were housed at 28 ± 2 °C with a 12 h light / dark cycle.
[0045] Mice were randomly divided into a blank control group (n=3), a lutein group (3 mice at each time point), and a lutein composite nanoparticle group (3 mice at each time point). All groups were fed with a normal diet for 1 week, during which they were free to eat pelleted feed and drinking water. After fasting for 12 h, lutein was added to flour slurry according to body weight and gavaged, while the blank control group was gavaged with flour slurry only. The bioavailability of lutein was measured at 0.5, 1, 1.5, 2, 4, 8, 12, and 24 hours after gavage.
[0046] Mice were killed by rapid CO2 anesthesia at a predetermined time after gavage. Blood was collected into heparin-coated tubes by cardiac puncture and centrifuged at 4°C to collect plasma. Liver, mesenteric adipose tissue, and eyeballs were collected, rinsed with cold saline, and immediately frozen in liquid nitrogen and stored.
[0047] A 2:1 volume ratio of dichloromethane:methanol solution was added to the plasma and vortexed for 1 min. Hexane was added to the mixture, mixed thoroughly, and centrifuged to collect the resulting upper hexane / dichloromethane layer. The bottom layer was extracted twice with dichloromethane and hexane. The upper extracts were combined and dried under nitrogen for analysis.
[0048] The liver, mesentery and eyeball were homogenized with normal saline. The homogenates were used for the extraction of lutein. The extracts were saponified with 10 mol / L potassium hydroxide at 60°C for 45 min to separate the lutein. Lutein was extracted from tissues according to the procedure described for plasma. All homogenization, saponification and extraction procedures were performed at 4°C under dim yellow light to minimize photoisomerization and oxidation of the lutein. The amount of lutein was determined by measuring the absorbance.
[0049] The results are detailed in the instruction manual. Figure 1-4 .
[0050] Comparative analysis of results
[0051] Attached Figure 1 This indicates that the structure of lutein was not destroyed during the synthesis of the composite particles. Figure 2 The results showed that the synthesized composite particles self-assembled into uniformly dispersed spherical nanoparticles in water with a particle size of about 100 nm. The particle size of the pure graft copolymer after separation was reduced to about 40 nm, indicating that the unreacted lutein was encapsulated in the polyacrylic acid grafted lutein copolymer nano-micelles; Figure 3 The results showed that the saturated solubility and bioaccessibility of the synthesized composite particles were 78-90 times and 3-5 times higher than those of lutein, and 25-30 times and 7-8 times higher than those of commercially available water-soluble lutein micropowders. Figure 4 The results showed that the bioavailability of the synthesized composite particles in plasma was increased by 6 to 8 times compared with lutein, and also promoted the accumulation of lutein in the liver, mesenteric tissue and eyeball.
[0052] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing water-soluble lutein composite nanoparticles, characterized in that The steps include: S1: dissolving polyacrylic acid in water to prepare an aqueous solution with a mass concentration of 30%, and refluxing for a period of time to remove the existing oxidizing initiator; S2: freeze-drying the polyacrylic acid solution obtained by reflux in step S1 for 24 hours, and then dissolving it in a certain amount of anhydrous tetrahydrofuran solution for later use; S3: adding a certain amount of lutein, dicyclohexylcarbodiimide and 4-dimethylaminopyridine to the solution prepared in step S2, stirring and reacting for a certain time at a certain temperature and in the dark, and setting aside; S4: evaporating the solvent after the reaction in step S3 by vacuum distillation at 45° C. for 1 h, adding deionized water of the same volume as the solution prepared in step S2 to complete the self-assembly of the amphiphilic copolymer, and preparing water-soluble lutein composite nanoparticles by freeze drying for 24 h; In the mixed solution described in step S3, the mass ratio of lutein to polyacrylic acid is 1:4 to 1:1, and the lutein is calculated as pure product; The mass ratio of lutein to dicyclohexylcarbodiimide and 4-dimethylaminopyridine in step S3 is 284:103-412:6.1, and the lutein is calculated as pure product; The stirring reaction temperature in step S3 is 25-45° C., and the stirring reaction time is 4-12 hours.
2. A method for preparing the water-soluble lutein composite nanoparticles according to claim 1, characterized in that: The reflux time described in step S1 is 6 to 24 hours.
3. A method for preparing the water-soluble lutein composite nanoparticles according to claim 1, characterized in that: The mass ratio of anhydrous tetrahydrofuran to polyacrylic acid described in step S2 is 10: 1 to 100:
1.
4. A water-soluble lutein composite nanoparticle prepared by the method according to any one of claims 1 to 3, characterized in that It can be made into tablets, capsules, powders, pastes or solutions by adding pharmaceutically or functional food acceptable excipients.